The Effectiveness of Adobe Animate Application-Based Learning Media in Improving Elementary School Students’ Understanding - Jayawi, Sakra Mansum; Kurniawati, Wiwien; Muzakkir (UNDIKMA, 2026)
This study examined the effectiveness of Adobe Animate application-based learning media in improving fifth-grade students’ understanding of science, particularly the topic of human organs, at SDN 1 Labuan Pandan in the 2024/2025 academic year. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. Data were collected through tests, observations, and documentation, and analyzed using Two-Way ANOVA and N-Gain tests with SPSS. The results showed that Adobe Animate-based learning media significantly improved students’ understanding. The Two-Way ANOVA indicated significant effects of learning media, gender, and their interaction (F = 4.43; 13.41; and 19.70, respectively; F_table = 4.15; α = 0.05). The experimental class achieved a higher average post-test score (86.56) and N-Gain value (0.7, moderate–high) compared to the control class (51.56; N-Gain = 0.1, low). Normality and homogeneity assumptions were met, and the R² value of 0.705 indicated that 70.5% of the variance in students’ understanding was explained by the learning media, gender, and their interaction. These findings confirm that Adobe Animate-based learning media are effective in enhancing fifth-grade students’ understanding of science concepts